การประเมินความสัมพันธ์ทางพันธุกรรมของพืชครามสกุล Indigofera ด้วยเทคนิคไอเอสเอสอาร์ - ธนานันต์, ธีระชัย; บัวบาน, ศุภรัตน์; ธนานันต์, นฤมล (Thai Journal of Science and Technology, 2020)
Indigo dye from many indigo plants can dye the fabric into a blue shade. In the Northeastern Thailand, Indigofera is used as the main raw material for indigo production. Since the Indigofera plants have high biodiversity, this research aimed to evaluate the genetic relationships of 15 Indigofera samples using inter-simple sequence repeats (ISSR) with 35 primers. Ten ISSR primers could clearly increase the DNA amplification product and a total of 225 bands (100 %) with the sizes of 515 to 3,000 base pairs from DNA fingerprints showed polymorphism. A dendrogram using NTSYS-pc version 2.01e was constructed by unweighted pair group method with arithmetic mean (UPGMA). The coefficients of similarity were between 0.09-0.68, and could separate 15 Indigofera samples into 7 groups. The results of this research can be used to plan for further conservation and breeding.